What to Expect From the Evolving Field of Geriatric Cardiology - Bell, Susan P; Orr, Nicole M; Dodson, John A; Rich, Michael W; Wenger, Nanette K; Blum, Kay; Harold, John Gordon; Tinetti, Mary E; Maurer, Mathew S; Forman, Daniel E (Journal of the American College of Cardiology, 2015)
The population of older adults is expanding rapidly, and aging predisposes to cardiovascular disease. The principle of patient-centered care must respond to the preponderance of cardiac disease that now occurs in combination with the complexities of old age. Geriatric cardiology melds cardiovascular perspectives with multimorbidity, polypharmacy, frailty, cognitive decline, and other clinical, social, financial, and psychological dimensions of aging. Although some assume that a cardiologist may instinctively cultivate some of these skills over the course of a career, we assert that the volume and complexity of older cardiovascular patients in contemporary practice warrants a more direct approach to achieve suitable training and a more reliable process of care. We present a rationale and vision for geriatric cardiology as a melding of primary cardiovascular and geriatrics skills, thereby infusing cardiology practice with expanded proficiencies in diagnosis, risks, care coordination, communications, end-of-life, and other competences required to best manage older cardiovascular patients.